TINJAUAN YURIDIS TINDAK PIDANA PENYEROBOTAN TANAH ADAT DI KABUPATEN TORAJA UTARA - Jenri Ranteallo; Yana Sukma Permana (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2022)
Land grabbing is not a new problem that often occurs in Indonesia. Unlawful land grabbing is an unlawful act and can be classified as a criminal act. The formulation of the problem in this study is the regulation of customary land ownership in North Toraja district and legal settlement of criminal acts of land grabbing in North Toraja district. Ownership of customary land is marked by physical possession and recognition as stated in Article 24 paragraph (2) of Government Regulation Number 24 of 1997. Regarding customary land or Toraja indigenous people, it is called tongkonan land. The North Toraja government has ratified Regional Regulation number 1 of 2019 concerning